Notes on some Oriental Derbidae (Hemiptera: Fulgoroidea) with description of new species - Szwedo, Jacek; Adamczewska, Malgorzata (Zootaxa, 2004)
The species described in the genera Losbanosia Muir and Nomuraida Matsumura are discussed, as well as the priority of these generic names. Two new species Losbanosia tamdaoensis sp. nov. from Tam ao National Park in Viet Nam and Losbanosia taivaniae sp. nov. from Taiwan are described. The distribution of species ascribed to the genus Losbanosia Muir is discussed.